Capacidade para autocuidado de pessoas hospitalizadas em setor clínico - Derigge, Jennifer de Mello; Oliveira, Andressa Rueda; Zamarioli, Cristina Mara (Universidade Federal de São Carlos, 2024)
To identify the capacity for self-care of people hospitalized in a clinical sector. Method: This is an observational, descriptive and cross-sectional study, carried out in an adult clinical inpatient unit, the included participants met the proposed eligibility criteria. Data were collected through interviews, which were guided by the instruments: Participant Characterization Form and Revised Self-Care Agency Assessment Scale (ASAS-R) and were analyzed based on descriptive statistics. Results: 90 patients participated in the study, there was a predominance of men, with an average of 60.08 years of age, education with a predominance of incomplete primary education, married and retired. The average number of days of hospitalization was 5.52 days and the majority of people interviewed reported using medications daily. The study revealed that the population hospitalized in a clinical sector has deficits in self-care capacity, as participants have an average of 53.74 in this aspect. The means of the factors Having power, Developing power and Lacking power for self-care were 22.73, respectively; 18,36 and 12. Conclusion: The results of the present study show that the self-care capacity of people hospitalized in a clinical sector is reduced.
Agenccy for self-care of people hospitalized in clinical sector
Keywords: Enfermagem; Autocuidado; Teorias de enfermagem; Nursing; Self care; Nursing theory; CIENCIAS DA SAUDE::ENFERMAGEM